DIMENSI SYARIAH COMPLIANCE PADA OPERASIONAL BANK SYARIAH - Miti Yarmunida (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2018)
Label Bank Syariah is not only a name, the consequences of the name impact on all aspects of its operations. Sharia Bank Operations must / must comply with the principles of sharia (Sharia Compliance). Broadly speaking there are seven dimensions of shariah compliance in the operations of Islamic Banks as follows: 1) does not contain elements of usury, 2) avoid bai 'al-inah, 3) does not contain gharar, 4) does not contain maisir, 5) Business run based on (7) Managing zakat, infaq and shadaqah in accordance with syariah